2018
DOI: 10.1080/15379418.2019.1568948
|View full text |Cite
|
Sign up to set email alerts
|

Are children better witnesses than adolescents? Developmental trends in different false memory paradigms

Abstract: The current study compared older children 's (11/12-year-olds) and adolescents ' (14/15-year-olds) vulnerability to false memory creation using two different methods (i.e., the Deese/ Roediger-McDermott [DRM] and memory conformity paradigms) involving neutral and negative stimuli. In line with previous research, a developmental reversal effect was found for the DRM paradigm, which means that when employing this method children displayed lower false memory levels than adolescents. However, when using the mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
0
6
0
1
Order By: Relevance
“…At this point, we cannot speak to the particular moderators that are likely to exist for false memory implantation for repeated events. Different types of false memories are not necessarily correlated (Calado et al, 2018;Falzarano & Siedlecki, 2019;Ost et al, 2013, Zhu et al, 2013. Despite being elicited via the same method (i.e., lost-in-the-mall-paradigm), it could be the case that false memories for repeated events and false memories for single events are elicited due to distinct mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…At this point, we cannot speak to the particular moderators that are likely to exist for false memory implantation for repeated events. Different types of false memories are not necessarily correlated (Calado et al, 2018;Falzarano & Siedlecki, 2019;Ost et al, 2013, Zhu et al, 2013. Despite being elicited via the same method (i.e., lost-in-the-mall-paradigm), it could be the case that false memories for repeated events and false memories for single events are elicited due to distinct mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The implications of this review should be drawn with care, however, because spontaneous false memories as induced by the DRM paradigm are typically weakly related or even unrelated to false memories induced by suggestion (e.g., D. M. Bernstein, Scoboria, Desjarlais, & Soucie, 2018; Calado, Otgaar, & Muris, 2019; Nichols & Loftus, 2019; Ost et al, 2013; Otgaar & Candel, 2011; Patihis, Frenda, & Loftus, 2018; Zhu, Chen, Loftus, Lin, & Dong, 2013). So, although psychopathology seems to be related to an increased vulnerability for spontaneous false-memory production, this does not necessarily imply that it is also linked to an increased susceptibility to suggestion-induced false memories.…”
Section: Psychotherapeutic Techniques Memory Distortions and Other mentioning
confidence: 99%
“…Many studies have observed a developmental reversal of the DRM effect, where false memories are higher for young adults compared to children (e.g., Brainerd et al, 1995 , 2004 ; Dewhurst and Robinson, 2004 ; Howe et al, 2004 ; Howe, 2005 ; Lampinen et al, 2006 ; Dewhurst et al, 2007 ; Anastasi and Rhodes, 2008 ; Calado et al, 2019 ). Fuzzy Trace Theory predicts that false memories will increase with age, because children have yet to develop the same extensive level of semantic networks that adults possess ( Brainerd et al, 2006 ).…”
Section: Resultsmentioning
confidence: 99%